1956
DOI: 10.1149/1.2430322
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Oxidation of Niobium

Abstract: Niobium oxidizes according to the linear rate law from 400~176 (14.7-605 psia O2). The oxidation rate is extremely pressure sensitive above 550~ Theoretical considerations indicate that an equilibrium adsorption process occurs prior to the rate-determining step. It was necessary to include a term in the rate equation for the interaction between the adsorbed molecules to interpret results above 650~ The interaction energy is influenced by the initial orientation of the metal surface. The activation energy for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1965
1965
1995
1995

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…According to the results of [232] the activation energy of niobium oxides in pure oxygen is aboutl 0 kcal/mole at 500-600°C.…”
Section: Interaction With Oxygenmentioning
confidence: 98%
“…According to the results of [232] the activation energy of niobium oxides in pure oxygen is aboutl 0 kcal/mole at 500-600°C.…”
Section: Interaction With Oxygenmentioning
confidence: 98%
“…A study by Bridges and Fassell (1956) shown that the oxide formed on niobium in air at 473 K (200°C) is adherent and prevents further oxidation (Fansteel, 1945). They also referred to works that found that niobium obeys the parabolic rate law from 473 to 548 K (200-275°C) (Phelps et al, 1946;Gulbransen and Andrews, 1949;Gulbransen and Andrews, 1950).…”
Section: Review Of Literature Datamentioning
confidence: 99%
“…Figure 26 shows an example of the specimen curvature from this set. Figures 27,28,29,and 30 show the reproducibility of the oxidation, cooling, dissolution, and annealing measurements respectively for specimens oxidized for 240 minutes. Figure 31 shows an example of the corresponding curvatures for this set of speci mens.…”
Section: Resultsmentioning
confidence: 99%
“…At 900°C the rate goes through a second maxi mum, experiences a slight drop, goes through a minimum around o o 1000 C and then increases again to 1400 C. This second reversal in the oxidation rate was usually associated with the transformation of niobium pentoxide from a low temperature to a high temperature form; called M-T or ) Y-«. The first reversal in the oxidation rate has been the subject of investigation of many researchers (12,24,26,29,48,50,55). The strongest evidence between oxidation rate and possible causes appears to be the correlation between the reversal in the oxidation rate and the change in the innermost oxide from NbOg to NbO as reported by Doyle (12).…”
Section: Oxidation/temperature Relationshipsmentioning
confidence: 97%